Price stickiness-income inequality nexus, impact on monetary policy in Nigeria - Samuel Oweh Abang; Kenneth Onaiwu Arasomwan; Oluwafemi Ayodele; Nkechi Stella Omang (Generasi Sains Indonesia, 2024)
This study examines the impact of price stickiness-income inequality nexus, om monetary policy in Nigeria from 1984 to 2023. The model formulated depicts monetary policy rate (MPR) as the dependent variable while gross domestic product (GDP), nominal exchange rate (NER), inflation (INF), interest rate (INT), consumer price index (CPI) as a measure of price stickiness and income inequality (IND) are independent variables. These data were sourced and extracted from CBN Statistical Bulletin. The study employed the OLS, Cochrane Orcutt and the chain rule to find the transmission mechanism. The ADF test reveals that the variables were all stationary at level. The study recommends that Monetary authorities are also encouraged to decrease the MPR. This will allow the banks to have enough cash to give to industries, the manufacturing sector and especially the small and medium enterprise. This will thus lead to creating of jobs to will lead to a balance or reduction in the income inequality It decreases interest rate and therefore encourages lending and investment and by extension, increase in output. Monetary authorities must however be wary of the tendency of an increase in money supply to lead primarily to inflation. Monetary authorities must ensure viable productive potentials in the economy respond positively to the rise in money supply.